PELAKSANAAN EKSTRAKURIKULER SENI TARI DI SMA INSTITUT NASIONAL SJAFE’I (INS) KAYUTANAM - Alhit Tamaranti; Zora Iriani; Nerosti Nerosti (FBS Universitas Negeri Padang, 2018)
AbstractThis study was aimped to analyze and describe the extracurricular implementation of dance art activity in SMA INS Kayutanam. Type of this study was qualitative with analytical descriptive method. The study object was implementation of dance art activity in SMA INS Kayutanam which were done by 5 students of class IX. Type of data in this study were both primary and secondary, and it used instrument namely the researcher. Technique of data collection was using library research. Observation, interview and documentation. Result of this study showed that the extracurricular implementation of dance art in SMA INS Kayutanam at class XI which was held as much as six times of meeting with using expositoric and Heuristic Strategy were able to improve students motion technique. In the first, second and third meeting, teachers combined both teachers model expositoric and students model expositoric. In the fourth, fifth and the last meeting, teachers Heuristic strategy with combined three models namely pure model, guided model, dan modifed model. With the strategies, teachers were able to manage the extracurricular implementation of dance art well and grew capability of students motion technique in dancing. Keywords: Extracurricular, Expositoric Strategy, Heuristic Strategy